2001
DOI: 10.1063/1.1358183
|View full text |Cite
|
Sign up to set email alerts
|

Spectra of random matrices close to unitary and scattering theory for discrete-time systems

Abstract: We analyze statistical properties of complex eigenvalues of random matrices close to unitary. Such matrices appear naturally when considering quantized chaotic maps within a general theory of open linear stationary systems with discrete time. Deviation from unitarity are characterized by rank M and eigenvalues Ti, i = 1, ..., M of the matrixT =1 − †Â . For the case M = 1 we solve the problem completely by deriving the joint probability density of eigenvalues and calculating all n− point correlation functions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…Similar effects were discussed in relation to the unimolecular decay in N O 2 molecules [21]. In section 4 we discuss this issue for the regime of weak non-Hermiticity.Most of our own results discussed in this review were reported earlier in the form of short communications [36,51,52,57,61,62,63] and in an unpublished paper by one of the authors [64]. Some (but by far not all) details of the underlying derivations are elucidated in the present text, as far as space restrictions allow.…”
mentioning
confidence: 52%
See 3 more Smart Citations
“…Similar effects were discussed in relation to the unimolecular decay in N O 2 molecules [21]. In section 4 we discuss this issue for the regime of weak non-Hermiticity.Most of our own results discussed in this review were reported earlier in the form of short communications [36,51,52,57,61,62,63] and in an unpublished paper by one of the authors [64]. Some (but by far not all) details of the underlying derivations are elucidated in the present text, as far as space restrictions allow.…”
mentioning
confidence: 52%
“…(96) is that it allows for calculation of all n−point correlation functions for arbitary N, n, M with help of the method of orthogonal polynomials. Again, the particular case M = 1 [62] is quite instructive and can be recommended to follow first for understanding of the general formulae outlined below.…”
Section: Rank M > 1 Deviations From Unitaritymentioning
confidence: 99%
See 2 more Smart Citations
“…. , 1) with |a| < 1 was calculated by Fyodorov [6] (see also [7]), up to a proportionality. The starting point was the formula for the joint eigenvalue distribution…”
Section: The K-point Correlationmentioning
confidence: 98%